2017
DOI: 10.5267/j.ijiec.2017.1.001
|View full text |Cite
|
Sign up to set email alerts
|

A two-layer genetic algorithm for the design of reliable cellular manufacturing systems

Abstract: This study presents a new mathematical model for the design of reliable cellular manufacturing systems, which leads to reduced manufacturing costs, improved product quality and improved total reliability of the manufacturing system. This model is expected to provide a more noticeable improvement in time and solution quality in comparison with other existing models. Each part to be manufactured may select each of the predefined manufacturing routes, such that the total reliability of the system is increased. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Other research focused on diverse imperfect features of manufacturing systems can also be found (e.g. Makis, 1998;Eroglu & Ozdemir, 2007;Chakraborty et al, 2013;Kaylani et al, 2016;Majumder et al, 2016;Zhang et al, 2016;Khanna et al, 2017;Rezazadeh & Khiali-Miab, 2017;Shakoor et al, 2017;Al-Bahkali & Abbas, 2018;Pearce et al, 2018). Because few studies focuse on multiproduct fabrication system by considering an expedited rate and scraps, this research aims to fill the gap.…”
Section: Introductionmentioning
confidence: 99%
“…Other research focused on diverse imperfect features of manufacturing systems can also be found (e.g. Makis, 1998;Eroglu & Ozdemir, 2007;Chakraborty et al, 2013;Kaylani et al, 2016;Majumder et al, 2016;Zhang et al, 2016;Khanna et al, 2017;Rezazadeh & Khiali-Miab, 2017;Shakoor et al, 2017;Al-Bahkali & Abbas, 2018;Pearce et al, 2018). Because few studies focuse on multiproduct fabrication system by considering an expedited rate and scraps, this research aims to fill the gap.…”
Section: Introductionmentioning
confidence: 99%
“…2 Literature review on hybrid GA techniques in CMS CMS problems and their different variants have been widely studied in literature (Paydar et al, 2013;Messaoudi and Rebaï, 2014;Mousavi et al, 2018). A majority of these techniques use GA (Karthikeyan et al, 2016;Moradgholi et al, 2016;Rezazadeh and Khiali-Miab, 2017;Vitayasak et al, 2017) and GA-based hybrid techniques (Chaudhuri et al, 2017;Costa et al, 2017). An extensive review on the application of GA and its hybridisations in CMSs have been done by Chaudhuri et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al [14] presented multi-objective hybrid algorithms for layout optimization in multirobot assembly for solving the cellular manufacturing problems. Rezazadeh and Khiali-Miab [15] developed a novel mathematical model for designing the reliable cellular manufacturing systems, which led to decrease in manufacturing costs, improved total reliability of the manufacturing system, and improved product quality. In addition, a two-layer genetic algorithm was presented to address the complexity of cell formation problems to obtain near optimal solutions.…”
Section: Introductionmentioning
confidence: 99%